Pobreza e privação social na área urbana de Santa Maria, Rio Grande do Sul: uma análise a partir dos usos do território - Spode, Pedro Leonardo Cezar (2020)
Urban Geography has been using various concepts and approaches for the analysis of urban socio-spatial and territorial inequalities over the decades. In this sense, to conduct this study, two concepts were used as the guiding thread of the research: social deprivation and the territory used. Thus, the main objective of this paper is to understand urban poverty from social deprivation and to materialize this concept in the urban territory of Santa Maria, Rio Grande do Sul. The method that underlies the research is the dialectic, in its elaborated foundation by the critical theory. As methodological procedures, we used the bibliographic review of the narrative type, the construction of a social deprivation index for the urban area of Santa Maria, as well as the collection of secondary data related to the use of the territory in the city, with the help of observation and fieldwork. The social deprivation index was methodologically elaborated from three dimensions to think about social deprivation: the education dimension, the income dimension and the household-sanitation dimension, through five social indicators constructed using the Brazilian Institute of Geography and Statistics (2010) variables. These data point to a certain spatial design of poverty in the city, linked to the center-periphery pattern, concentrating deprivation mainly in the peripheral regions, such as the North, Northeast, South and West of the urban area, but with deprivation spots occurring discontinuously in other areas. of the city. In this sense, through the social deprivation index, together with the field incursions, three major areas of deprivation were classified in the urban territory of Santa Maria: the first crossing the northern extension of the urban area, which begins in the northern zone of Camobi, following discontinuously through the neighborhoods. from the Northeast and North, following the railroad. The second deprivation area starting in the North region, passing through areas of the Midwest and West region such as Noal, Nova Santa Marta and Agro-Industrial. In addition to these, a third in the southern region, extending to the Center East, between the neighborhoods Urlândia, Lorenzi and Diácono João Luiz Pozzobon. The areas of low deprivation are concentrated mainly in the Center, extending to the east of the city, towards the Camobi neighborhood. In this sense, poverty and social deprivation are relative in space and territory, determined by the historical process of territorial use in these regions. To better understand this dynamic, we selected land uses that associate poverty and social deprivation, such as the Industrial District, the landfill, the State Presidio, the railroad apparatus, the military presence, among others. Thus, it deepened in relation to three major space structures: the railroad tracks, the Arroio Cadena and the Morro Cechella, where the poor of the city converge or the slow men of Milton Santos. These three prominent spatial forms, namely the Arroio Cadena, the railway apparatus and the Morro Cechella, within the context of the production of territorial uses, appear to be associated with different forms of deprivation, especially the deprivation of access to urban housing. Therefore, housing deprivation, reflected by the phenomenon of irregular occupations in the urban area of Santa Maria, is explicitly shown to be one of the main deprivations in the territory.